(untitled) (Scientia Agropecuaria, 2024)
The relevance of this research is associated with the great potential of using montmorillonite clay for the treatment and prevention of infectious diseases of important farm animals and the lack of knowledge of these issues in modern literature. The paper was aimed at studying the toxicity, therapeutic and prophylactic efficacy of a veterinary drug developed based on montmorillonite clay of Western Kazakhstan for bovine gastroenteritis. The paper involved clinical, laboratory and pathoanatomical research methods. The obtained data were analysed using statistical methods. Oral administration of the developed veterinary drug did not have a significant effect on the parameters of the biochemical blood test of rats (p > 0.05) and the morphology of their internal organs after 2 weeks. The developed drug does not have toxicity; it can be attributed to the class of low-hazard substances. With a high degree of probability (p < 0.05), it can be argued that the veterinary drug improves the results of the standard treatment regimen for acute gastroenteritis in Kazakh whitehead cattle by 15%-30%. With a probability of 95%, it can be argued that the addition of the developed veterinary drug to the diet for 30 days led to a decrease in the incidence of gastroenteritis by 2.3 - 3.5 times among cattle. In addition, metabolic processes in the body of animals significantly (p < 0.05) improved in the three experimental groups, compared with the control group, in which cattle received a standard diet. Pathological and anatomical study and histological examination of organs and tissues of cows did not reveal significant differences between animals from the experimental and control groups. The results obtained may be useful in the development of effective methods for the treatment and prevention of gastroenteritis in cattle.